(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The physico-chemical properties of a compound that are considered important include its molecular structure, solubility, ionization and vapour pressure. All these characteristics affect the toxicological and pharmacological properties of the compound. The nature of chemical reaction is determined by the functional groups of the substance and its toxicity is a response of organisms consequent upon reaction between the compound and certain part of the organism.The non-polar (lipophilic) confounds are highly soluble in lipids and other organic solvents. Therefore, they can easily penetrate the membrane’s lipoprotein layers and produce their potential effects. However, polar (hydrophilic) compounds are not soluble in lipids therefore, they cannot cross the membrane barrier to reach the target site. Other properties of chemicals such as rate constant for hydrolysis, photolysis, evaporation, sorption and partition coefficients are also important and affect environmental concentration of toxicants.